2001
DOI: 10.1038/sj.ijo.0801697
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous adipose tissue layers as a stable correlate of leptin in response to short term energy restriction in obese girls

Abstract: AIMS:We studied the relationship of subcutaneous adipose tissue layers (SAT-layers) measured at 15 specified body sites with leptin before and after a weight loss program for three weeks. SUBJECTS AND METHODS: In 70 obese girls, SAT-layers were measured by means of the optical device, lipometer. Fat mass (FM) was estimated by means of bioelectrical impedance. RESULTS: At the beginning of the study, all estimates of adiposity, insulin, and SAT-layers from the upper body (from 1 -neck to 6 -lateral chest) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Our observation of a positive correlation between plasma leptin levels and IGF-1 in children with short stature complements previous studies in prepubertal [31] and peripubertal [32] children and in children with severe malnutrition [33]. As it has been demonstrated that body fat mass is a main determinant for plasma leptin levels [4,5,19,28,34] and IGF-1 is positively correlated with nutritional status [23,35], the close relationship between plasma leptin levels and IGF-1 can be explained. This finding is supported by our data demonstrating higher IGF-1 levels in patients with higher BMI.…”
Section: Discussionsupporting
confidence: 86%
“…Our observation of a positive correlation between plasma leptin levels and IGF-1 in children with short stature complements previous studies in prepubertal [31] and peripubertal [32] children and in children with severe malnutrition [33]. As it has been demonstrated that body fat mass is a main determinant for plasma leptin levels [4,5,19,28,34] and IGF-1 is positively correlated with nutritional status [23,35], the close relationship between plasma leptin levels and IGF-1 can be explained. This finding is supported by our data demonstrating higher IGF-1 levels in patients with higher BMI.…”
Section: Discussionsupporting
confidence: 86%
“…The researchers suggest that the obese individuals with appropriate baseline levels are more sensitive to environmental factors; therefore, they are more likely to respond to intervention programmes. Overall, leptin changes during interventions are best determined by initial leptin concentrations [120,139,140,[142][143][144]. This insight is important in understanding the predictive ability of leptin for an individual's ability to lose body fat and to act as a biological marker in childhood obesity.…”
Section: Leptin Energy Balance and Exercise Interventionmentioning
confidence: 98%
“…In addition to the functional distinction of subcutaneous adipocytes from different layers, there is significant divergence in subcutaneous adipocyte characteristics or function even within a layer (1,14–17). In swine, outer layer subcutaneous adipocytes located in distal locations are less lipogenic than outer layer subcutaneous adipocytes in more proximal locations (1).…”
mentioning
confidence: 99%
“…In swine, outer layer subcutaneous adipocytes located in distal locations are less lipogenic than outer layer subcutaneous adipocytes in more proximal locations (1). In man, distal and proximal subcutaneous adipocytes respond differentially to weight loss and account for serum leptin levels to different degrees (15,16). Furthermore, non‐insulin dependent diabetes mellitus is associated with an increase in more proximal (upper trunk) subcutaneous adipose tissue accretion in men and women (17,18) and a decrease in distal (lower leg) subcutaneous adipose tissue accretion in women (17).…”
mentioning
confidence: 99%